Scofflaw bicycling: Illegal but rational - Wesley E Marshall; Daniel Piatkowski; Aaron Johnson (Journal of Transport and Land Use)
Nearly everyone has jaywalked, rolled through a stop sign, or driven a few miles per hour over the speed limit, but most such offenses face no legal consequences. Society also tends to see these relatively minor infractions that almost all people make—though they are unmistakably illegal—as normal and even rational. Bicyclists who break the law, however, seem to attract a higher level of scorn and scrutiny. While the academic literature has exhaustively covered unlawful driving behaviors, there remains little research on bicyclists who break the rules of the road. This paper examines rule-breaking bicyclists and the factors associated with such behaviors. We also explore the question: are bicyclists making rational, albeit illegal, choices—similar to most drivers and pedestrians—or are bicyclists reckless and dangerous? Because it’s proven effective for reaching hard-to-reach populations, we employed a snowball-sampling framework and an online, scenario-based survey completed by nearly 18,000 respondents. Via multi-level statistical analyses, our results suggest that younger people and males tend to exhibit higher levels of illegal bicycling behavior, but even when combining high-risk factors, the overwhelming majority of bicyclists are not reckless. Controlling for the context and social norms of the city where one lives tends to outweigh individual bicyclist characteristics such as race/ethnicity and income. Unlawful drivers and pedestrians tend to rationalize their behaviors as time saving; bicyclists similarly rationalize their illegal behaviors but were more inclined to cite increasing their own personal safety and/or saving energy. Most bicyclists can generally be described as rational individuals trying to function safely and efficiently given the context and norms of where they live and the transportation system put in front of them.